Aplikasi Animalpedia Berbasis Android sebagai Media Pembelajaran Materi Kingdom Animalia - Intan Delia Tivania Putri; Sonia Dianita Savitri; Intan Dwi Puspitasari; Ramadhani Nur Aisyah; Fajar Eric Firmansyah; Reni Ambarwati (Universitas Sebelas Maret, 2017)
Advancement in science and technology, especially in android operating system encourage renewal efforts in learning. The rise of android-based smartphone used among students can support them learning on Net Generation who prefer to visual media and gadget. This research aims to produce AnimalPedia application based on Android and to know its influence to increase student learning outcomes. The research was conducted by ASSURE development method which was tested to two classes namely control class with conventional learning and experimental class by using AnimalPedia application. The respondents used in the research were 20 tenth grade students of SMA Negeri 4 Sidoarjo on Kingdom Animalia subjects. Animalpedia application was created by using software named android studio. Methods of data collection was done by documentation method, expert validation, questionnaire, and test. The research parameters are expert validation, user response and student learning outcomes. This development research produced an Animalpedia Application containing splash screen, phylum information and information of each class, and side menu containing; KI and KD, Concepts, tutorials and authors that have been uploaded to the Google Play Store. The results showed that the application AnimalPedia can improve student learning outcomes of class X IPA SMA Negeri 4 Sidoarjo.